Molecular Screening of 43 Brazilian Families Diagnosed with Leber Congenital Amaurosis or Early-Onset Severe Retinal Dystrophy - Fernanda B. O. Porto (Genes, 2017)
Leber congenital amaurosis (LCA) is a severe disease that leads to complete blindness in children, typically before the first year of life. Due to the clinical and genetic heterogeneity among LCA and other retinal diseases, providing patients with a molecular diagnosis is essential to assigning an accurate clinical diagnosis. Using our gene panel that targets 300 genes that are known to cause retinal disease, including 24 genes reported to cause LCA, we sequenced 43 unrelated probands with Brazilian ancestry. We identified 42 unique variants and were able to assign a molecular diagnosis to 30/43 (70%) Brazilian patients. Among these, 30 patients were initially diagnosed with LCA or a form of early-onset retinal dystrophy, 17 patients harbored mutations in LCA-associated genes, while 13 patients had mutations in genes that were reported to cause other diseases involving the retina.